Troeltsch's eschatological absolute - Kuehn, Evan (AAR academy series, 2020)
""This study argues that the core of Ernst Troeltsch's theological project is an eschatological conception of the Absolute. Troeltsch developed his idea of the Absolute from post-Kantian religious and philosophical thought, and applied it to the Christian doctrine of eschatology. Troeltsch's eschatological Absolute must be understood in the context of questions being raised at the turn of the twentieth century by research on New Testament apocalypticism, as well as by modern critical methodologies in the historical sciences. The study is a revisionist response to common approaches to Troeltsch that read him as introducing problematic historicist and immanentist assumptions into Christian theology. Instead, it argues that Troeltsch's theological modernism presents a compelling account of the meaningfulness of history while retaining a commitment to divine transcendence that is unconditioned by history. As such, his theology remains relevant to theological research today, well beyond theological circles that normally take Troeltsch's legacy to contribute in a constructive way to their work. ""--